Continuous skill assessment form (Part 2) - Md Mustafa, Md Muziman Syah; Ahmad, Norsham (2020)
This continuous skill assessment form (Part 2) is developed as a tool to evaluate Optometry students' performance in conducting routine optometric tests and interpreting the results of the tests in Primary Optometry Clinic I. It includes ocular motility, vision near point convergence, amplitude of accomodation, retinoscopy, subjective refraction, addition (ADD) tests/procedure